KUALITAS PELAYANAN PENYEDIAAN AIR BERSIH OLEH PDAM TIRTA DUMAI BERSEMAI DI KOTA DUMAI TAHUN 2023 - Maharani, Rhisma; Rafi, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Clean water is an important element in everyday human life. Providing clean water is one of the responsibilities of the local government to ensure that the community has access to proper clean water. The Regional Drinking Water Company (PDAM) Tirta Dumai Bersemai is managed with the main objective to provide clean water services to the people of Dumai City, but in providing its services there has still been no optimal service and many public complaints about the services provided by PDAM in Dumai City. This study aims to describe the quality of clean water provision services by PDAM Tirta Dumai Bersemai in Dumai City in 2023 and to describe the factors inhibiting the quality of clean water provision services by PDAM Tirta Dumai Bersemai in Dumai City in 2023. The research approach used is a qualitative approach using a descriptive research type. The location of this research was conducted at PDAM Dumai City. Data collection techniques were carried out by interviews and documentation. Data analysis techniques are carried out by collecting data, reducing data, presenting data, and concluding. The results of this study indicate that the quality of clean water provision services by PDAM Tirta Dumai Bersemai in Dumai City is still less than optimal. This can be seen from direct evidence (tangibles) that PDAM Dumai City does not yet have adequate facilities. Likewise, with reliability, there are still many complaints felt by customers. In terms of responsiveness, PDAM Dumai City is less responsive because it does not provide an appropriate response to customer complaints. However, in terms of assurance and empathy, it has been assessed as optimal. The inhibiting factors are budget constraints and suboptimal quality of human resources. Keywords: Quality, Service, PDAM, Clean water provision